2013
DOI: 10.1007/978-3-642-38706-7_4
|View full text |Cite
|
Sign up to set email alerts
|

End-User Experiences of Visual and Textual Programming Environments for Arduino

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent Abstract.Arduino is an open source electronics platform aimed at hobbyists, artists, and other people who want to make things but do not necessarily have a background in electronics or programming. We report the results of an exploratory empirical study that investigated the potential for a visual programming environment to provide benefits with respect to efficacy and user exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 20 publications
1
43
0
2
Order By: Relevance
“…On assessment questions, Scratch students performed significantly better with conditionals, but not with loops. Booth and Stumpf [4] compared text and block interfaces for adults learning to program Arduino boards and found that the block group perceived the interface to be more friendly and experienced lower perceived workload. McKay and Kölling [24] used a cognitive modelling tool to predict the execution time of programming tasks in a variety of editors, including block, text and an early prototype of the Stride editor.…”
Section: Comparing Blocks and Textmentioning
confidence: 99%
“…On assessment questions, Scratch students performed significantly better with conditionals, but not with loops. Booth and Stumpf [4] compared text and block interfaces for adults learning to program Arduino boards and found that the block group perceived the interface to be more friendly and experienced lower perceived workload. McKay and Kölling [24] used a cognitive modelling tool to predict the execution time of programming tasks in a variety of editors, including block, text and an early prototype of the Stride editor.…”
Section: Comparing Blocks and Textmentioning
confidence: 99%
“…Após um levantamento na literatura comênfase nas principais plataformas atualmente disponíveis para programação visual voltados a robótica [Booth and Stumpf 2013, De Miranda et al 2007, Aureliano and Tedesco 2012, Queiroz et al 2016, cinco softwares merecem destaque: Ardublock [Ardublock 2017], Minibloq [Minibloq 2017 …”
Section: Softwares Utilizados No Ensino De Rpunclassified
“…O uso de Programming Assistance Tools (PATs) pode ser uma das alternativas incorporadas por professores no desenvolvimento estudantil, explorando conhecimentos como de raciocícinio lógico, robótica, eletrônica básica, entre outros para a motivação de discentes. Atualmente, o uso de linguagens visuais de programação tem se tornado muito pertinente, desta forma discute-se o uso destas como sendo uma representação visual que facilita a aprendizagem de programação [Booth andStumpf 2013, Price andBarnes 2015].…”
Section: Cenário De Usounclassified